Evolutionary algorithms and Evolutionary Particle Swarms (EPSO) in modeling evolving energy retailers - Vladimiro Miranda (2005)
This paper provides evidence that Evolutionary Particle Swarm Algorithms outperform Genetic Algorithms in deriving optimal strategic decisions for an Energy Retailer, in the framework of a complex simulation of a multiple energy market, based on an Intelligent Agent FIPA-compliant open source platform.